Identification and Epidemiology of Severe Respiratory Disease due to Novel Swine-Origin Influenza A (H1N1) Virus Infection in Alberta - George Zahariadis; Ari R Joffe; James Talbot; Albert deVilliers; Patricia Campbell; Kanti Pabbaraju; Sallene Wong; Nathalie Bastien; Yan Li; Robyn L Mitchell; Xiao-Li Pang; Stephanie Yanow; et al. (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: In March 2009, global surveillance started detecting cases of influenza-like illness in Mexico. By mid-April 2009, two pediatric patients were identified in the United States who were confirmed to be infected by a novel influenza A (H1N1) strain. The present article describes the first identified severe respiratory infection and the first death associated with pandemic H1N1 (pH1N1) in Canada.